1996
DOI: 10.1007/s002709900032
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Metal Stents for Palliative Treatment of Superior Vena Caval Syndrome

Abstract: The overall clinical success rate for long-term patency was 100% for the Z-stents and 69% for the new Wallstent. These results suggest that when used for this purpose, the new Wallstent is more thrombogenic at 2 weeks than the Z-stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Other stent types had 78–100% success rates in relieving the venous stenosis 15 3033. Reports for multiple stents used within the same institution achieved similar results 10 13 15 18 21 34. Thus the experience of the interventional radiologist is the key to achieving good results.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Other stent types had 78–100% success rates in relieving the venous stenosis 15 3033. Reports for multiple stents used within the same institution achieved similar results 10 13 15 18 21 34. Thus the experience of the interventional radiologist is the key to achieving good results.…”
Section: Methodsmentioning
confidence: 95%
“…Occult cerebral metastases may also explain brain haemorrhage during fibrinogen lysis 28. Massive haemoptysis may also occur during thrombolytic therapy34 or during maintenance anticoagulation therapy 20. Paraneoplastic hypercoagulation state combined with the presence of a foreign body increased the risk of thrombosis after stent placement.…”
Section: Methodsmentioning
confidence: 99%
“…Then in 1986, Charnsangavej et al 2 first reported employing the Gianturco stent in two patients, one with superior vena cava syndrome and the other with retroperitoneal fibrosis that obstructed the inferior vena cava (IVC), which resulted in immediate relief of the presenting symptoms. [3][4][5][6][7] The Japanese Society for the Study of Metallic Stents also reported that 149 Gianturco stents were placed in the venous system of patients in Japan between 1987 and 1993. [3][4][5][6][7] The Japanese Society for the Study of Metallic Stents also reported that 149 Gianturco stents were placed in the venous system of patients in Japan between 1987 and 1993.…”
Section: Introductionmentioning
confidence: 99%
“…A completa resolução da síndrome é relatada em 68 a 100% dos casos 12,[22][23][24][25] . O sucesso clínico do tratamento varia de 55 26 a 93% 12 .…”
Section: Discussionunclassified
“…A taxa de perviedade geral fica em torno de 77 a 85%, e assistida entre 85 e 91%, com seguimento de 17 meses 11,18,26 . As taxas de reestenose observadas variam de 0 a 45% 22,23 . Nos pacientes com lesões associadas à hemodiálise, a taxa de reestenose varia de 60 a 80% 27 .…”
Section: Discussionunclassified